(untitled) (Revista Brasileira de Contabilidade e Gestão, 2017)
This study aimed to show and analyze the Living Labs, a platform that arise as way to promote social innovation, which acts as an intermediator between users, companies and public institutions. The Living Labs were identified by means of mapping done on the internet and based on the history of members (active and non-active ones) associated with the European Network of Living Labs (EnoLL), which configures itself as an international federation of Living Labs. In Brazil, the existence of 12 Living Labs memberships to the EnoLL network was noted, however, only one continues as an active member. In addition to these, two other spaces with the nomenclature Living Lab were identified.